Beyond “Maria”: Charting a Course for Maternal Health Equity - Wendy Post (Health Equity)
Maternal mortality and morbidity are enduring public health crises disproportionately affecting Black, Indigenous, Hispanic, and other marginalized populations. This inequity highlights the necessity for a comprehensive, equity-driven framework to address systemic failures within maternal healthcare. Although the Maternal Mortality Review Information Application (MMRIA) provides valuable retrospective insights into maternal deaths, its capabilities must be expanded by integration with real-time interventions. Innovative approaches, including obstetric decompensation scoring tools like the Obstetric Early Warning Score and Maternal Early Warning Score (OEWS) and Maternal Early Warning Trigger systems, are strongly advocated. These predictive technologies, when integrated into electronic medical records, generate real-time alerts that enable clinicians to proactively mitigate complications before they escalate. Simulation-based training further complements these technologies, immersing healthcare teams in realistic, high-stress scenarios drawn directly from maternal mortality case studies. Such immersive programs effectively address implicit biases, enhance diagnostic accuracy, and foster cultural humility, particularly benefiting marginalized populations. Additionally, the establishment of Maternal Morbidity Review Committees (MMORCs) is proposed as a critical advancement, enabling multidisciplinary, immediate interventions during acute maternal events. Collectively, these innovations aim to transition maternal health care from a reactive to a proactive model, significantly improving maternal outcomes. Highlighted is the urgency for systemic reforms and data-driven interventions to eliminate inequities, prioritizing prevention, equity, and cultural humility to ensure maternal healthcare is equitable, accesible and inclusive.